2004
DOI: 10.1185/030079904125003197
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment of meta-analyses of RCTs of pharmacotherapy in major depressive disorder

Abstract: Despite quality guidelines, the average quality of published MAs of antidepressants is barely acceptable (50.2%). A need exists for adherence to standardized reporting and quality guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 69 publications
1
19
1
Order By: Relevance
“…Moreover, the quality of the way in which treatment meta-analyses were conducted and reported was not predicted by novel or more traditional measures of their impact in the scientifi c community after controlling for the lower citation rates observed for more recent reviews. The overall scores of the treatment meta-analyses included in this review on the QUOROM and ISQRO are consistent with the range of results (QUOROM, 9-12.3; ISQRO, 2.7-4.7) reported by other studies of the quality of meta-analyses of RCTs in the health sciences [4,21,27,29,30]. These results are also similar to those reported by Bereza and colleagues [31] in the only other review of meta-analyses of anxiety disorder RCTs.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Moreover, the quality of the way in which treatment meta-analyses were conducted and reported was not predicted by novel or more traditional measures of their impact in the scientifi c community after controlling for the lower citation rates observed for more recent reviews. The overall scores of the treatment meta-analyses included in this review on the QUOROM and ISQRO are consistent with the range of results (QUOROM, 9-12.3; ISQRO, 2.7-4.7) reported by other studies of the quality of meta-analyses of RCTs in the health sciences [4,21,27,29,30]. These results are also similar to those reported by Bereza and colleagues [31] in the only other review of meta-analyses of anxiety disorder RCTs.…”
Section: Discussionsupporting
confidence: 65%
“…However, others have either not detected this trend [27] or have attributed this fi nding primarily to improvements in the reporting of Cochrane reviews [7••]. Indeed, in the current study, removal of data for the Cochrane reviews reduces this temporal trend to nonsignifi cance.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…A 2004 study [10] that did not produce a similar result might be attributed to the fact that most of the articles it included were published before the release of the QUOROM statement, another evidence of its effectiveness.…”
Section: Discussionmentioning
confidence: 63%
“…But systematic reviews and meta-analyses may be prone to bias introduced in the identification, selection, or statistical analysis of included studies, and methods are often poorly reported. [2][3][4][5][6][7][8] The implication of poor reporting is that systematic reviews may reach incorrect conclusions, and as systematic reviews are often used to guide clinical practice, this may seriously affect the delivery of health care.…”
mentioning
confidence: 99%